EXAMINATION OF MOTOR SKILLS IN KINDERGARTEN - Josip Lepeš (Exercise and Quality of Life)
The purpose of the research was to study 680 children - 370 boys and 310 girls of to 5-7 year age, they were examined concerning their motor skill. It was found that physical advancement of children reaches, or more exactly exceeds the home references by 50 percent. Their physical advancement is a good base for the physical performances. Evaluated the motor skill of children it was found that in this age interval the girls are better in balancing compared to the boys. The growth rate of girls is also higher than that of the boys. These results are interpreted as characteristics of motion development at the end of the small child age. Uniform development rate was observed in running with evasion and in the two tests elaborated by our group, the boomerang running and the obstacle course. Reliability and validity of both tests were qualified excellent expect for one case. They are both recommended for practical use.